Appraisal of existing evidences of competition law and policy: Bilateral legislative developments of Sino-Pak - Nishan-E-Hyder Soomro; Wang Yuhui (Heliyon, 2023)
Developing nations use contemporary competition laws based on international models for reasons ranging from achieving international legitimacy to achieving domestic economic objectives. Although passing such laws gives these nations competition regimes more legitimacy, doing so does not guarantee that their economic goals will be met unless the laws are also effectively implemented. Comparative legal scholarship suggests that effective enforcement requires, among other things, a positive link between the passed laws and the nation's pre-existing legal systems in light of development economics. The globalization of national competition laws, particularly the application of international soft law, is responsible for the existence of modern competition law. Secondly, the competition regimes in Pakistan and China face a number of long-term difficulties, many of which are the product of globalization, which must be addressed as soon as possible. In order to examine the aims and objectives, this study employs qualitative data analysis. The results of this research suggest that for both nations to successfully implement competition law, innovation and unconventionality are required. Although the goal of competition law is to prevent anti-competitive activities and practices by promoting fair and open market competition, this goal is achieved through protecting consumers from businesses' use of unfair business practices. Because of this, the act encourages the formation of agreements that limit and restrict market dominance. In addition, the law specifies how investigations, acquisitions, mergers, penalties, leniency, and other aspects of law enforcement should be handled. As a result, this law can be seen as extremely important for regulating firms while maintaining consumer and producer welfare. It eventually supports economic growth and social justice. As a result, Voluntary adherence to competition law, rules, and regulations is essential since doing so would significantly lower the societal costs of enforcing the law.